2019
DOI: 10.1038/s41598-019-46636-4
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin response to intense nanosecond-scale electric field in molecular dynamics simulation

Abstract: Intense pulsed electric fields are known to act at the cell membrane level and are already being exploited in biomedical and biotechnological applications. However, it is not clear if electric pulses within biomedically-attainable parameters could directly influence intra-cellular components such as cytoskeletal proteins. If so, a molecular mechanism of action could be uncovered for therapeutic applications of such electric fields. To help clarify this question, we first identified that a tubulin heterodimer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 89 publications
3
56
1
Order By: Relevance
“…The kinesin dipole moment is pointing towards tubulin body (Fig. 2i–p), which has an overall negative charge 20 , as would be predicted by simple electrostatics. However, the kinesin net charge is also negative (−5 e for pH 7 - see Supplementary information S1, section Kinesin charge analysis ), which would suggest repulsive forces from tubulin, pointing to an intricate complexity of the kinesin-tubulin electrostatic interaction.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The kinesin dipole moment is pointing towards tubulin body (Fig. 2i–p), which has an overall negative charge 20 , as would be predicted by simple electrostatics. However, the kinesin net charge is also negative (−5 e for pH 7 - see Supplementary information S1, section Kinesin charge analysis ), which would suggest repulsive forces from tubulin, pointing to an intricate complexity of the kinesin-tubulin electrostatic interaction.…”
Section: Resultsmentioning
confidence: 61%
“…In principle, there is always a possibility to perform calculations on a longer time scale, on larger molecular systems or with higher physical accuracy. The time scale of our current simulations was 30 ns (three replicates for each condition), and the full atom molecular system was a kinesin motor domain docked on single tubulin - analyses of comparable times scale and molecular size are common in this field 2022 . While we consider these settings to be appropriate for the first solid assessment of ns electric field effect on kinesin nanomotor, we are aware of several avenues for future work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles have suggested that electric fields affect cell activity, and most of the proposed mechanisms are supported by numerical calculations. 9,11,[13][14][15][16][17] There are several applications for proteins exposed to high electric fields; for example, controlling intracellular electric fields may enable the manipulation of cell activities such as cell division, which may suppress tumor growth. 15,18 A previous study reported that a bacterial spore wall composed of peptidoglycan was damaged by intense pulsed electric fields with an intensity of 7.5 kV/cm.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is technically difficult to apply strong electric fields to liquid samples, most previous studies have used numerical calculations. 1719 According to such calculations, proteins change their three-dimensional structures under a static electric field of 1 MV/cm. Therefore, we focused on amyloid destruction theory, which speculates that amyloid is destroyed under fields stronger than 1 MV/cm which last longer than 400 ns.…”
Section: Introductionmentioning
confidence: 99%